To What Extent Have Cyber Sabotage and Cyber Espionage Undermined the National Security of South Africa, Kenya and Ethiopia, 2016- 22 - Kinnes, Shaun (University of the Witwatersrand, Johannesburg, 2024)
The state of cyber security in Africa presents a diverse and evolving landscape, with the continent possessing pockets of resilience, instead of a common agreed upon and ratified framework. This research report aims to highlight the state of cyber security in Africa, delving into legislative frameworks, cyber protocols, and responses. The world is changing, and with this change comes disruption, and disruption ultimately needs planning, you’re either at the table or on the menu. The report utilises South Africa, Kenya, and Ethiopia as case study countries to drive analysis into the disruptions and threats posed to the cyber landscape. The sophistication of cyber threats, which include ransomware and fraud coupled with disparities in cyber security capabilities across sectors and countries persist across the continent. Cybercrimes and cyber sabotage in the case of South Africa draw upon the close correlation between macroeconomic stability and cyber security, while geo-political tensions such as in the case studies of Kenya and Ethiopia show how states have begun a flirtation with cyber tools with the objective of pursuing foreign policy objectives.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Social Science, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cyber Offence; Cyber Defence; National Security; Cyber Espionage; Cyber Sabotage; Cyberspace; SDG-4: Quality education